2023
DOI: 10.1002/smll.202305303
|View full text |Cite
|
Sign up to set email alerts
|

Reversal in Output Current Direction of 4H‐SiC/Cu Tribovoltaic Nanogenerator as Controlled by Relative Humidity

Jinchao Xia,
Andy Berbille,
Xiongxin Luo
et al.

Abstract: Tribovoltaic nanogenerators (TVNG) represent a fantastic opportunity for developing low‐frequency energy harvesting and self‐powered sensing, by exploiting their real‐time direct‐current (DC) output. Here, a thorough study of the effect of relative humidity (RH) on a TVNG consisting of 4H‐SiC (n‐type) and metallic copper foil (SM‐TVNG) is presented. The SM‐TVNG shows a remarkable sensitivity to RH and an abnormal RH dependence. When RH increases from ambient humidity up to 80%, an increasing electrical output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…First, there is a need for improvement in the physical model of contactless TES. Second, it is observed that the charge on the triboelectric layer tends to dissipate in high relative humidity (RH) environments. , This phenomenon is attributed to the interaction of water molecules with the surface of the triboelectric layer and their ionization in response to the electrostatic field. This ionization process results in the neutralization of a portion of the charge .…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a need for improvement in the physical model of contactless TES. Second, it is observed that the charge on the triboelectric layer tends to dissipate in high relative humidity (RH) environments. , This phenomenon is attributed to the interaction of water molecules with the surface of the triboelectric layer and their ionization in response to the electrostatic field. This ionization process results in the neutralization of a portion of the charge .…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] To circumvent this problem, TVNGs with improved performance have been demonstrated even in high‐humidity environments based on materials that are stable in humid environments. [ 18,19 ] However, most TVNGs performed in high‐humidity environments adopt strategies to stabilize the surface state without fully utilizing the electrical properties of water molecules.…”
Section: Introductionmentioning
confidence: 99%